Self-attributed facial prominence on social networks through one's own photography: Effect of type of network, age and gender - Cifre, Eva; Santamaría-Dávila, Jordi; Rosel, Jesús F. (Anales de Psicología / Annals of Psychology, 2022)
There are many studies on Self-Attributed Face-ism (SAF) in considering social networks (SNS), sex and age, but with these variables separately. This research carries out a joint study of the above variables through a random sample of 1050 SNS profiles. Our hypothesis is that SAF is a function of SNS (dating: Badoo, social: Facebook, professional: LinkedIn), sex, age, and the interaction of sex×age. The results show differences in SAF depending on SNS (highest in the professional network), men having more facial prominence than women. It happens even more when they get older, whereas SAF hardly augments in women with age (having more body prominence than men) (sex x age interaction). Findings show that SAF on-line is a complex phenomenon, it seems not to have a unique and straightforward theoretical explanation, and SAF gender stereotypes grow with age. We also consider the need to study the phenomenon, including a gender perspective, to fight against sexism in new media.